(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1992)
On the Hyblean Plateau (south eastern Sicily) at Contrada Cimillà, south west of Ragusa, the infillings of a karstic cavity on the carbonatic Ragusa platform has yielded abundant Pleistocene mammal bones. Prevailing remains of thé pigmy megacerine Megaloceros (Megaceroides) carburangelensis (De Gregorio, 1925) are associated with scanty remains of Cervus siciliae Pohlig, Elephas cf. mnaidriensis Adams, Ursus cf. arctos L. aves. On the margins of the Hyblean Plateau two Pleistocene mammal faunal associations have been recognized which are contained in continental deposits correlated with early Middle Pleistocene and late Middle Pleistocene-Late Pleistocene terraced marine deposits, respectively. Both faunal associations are preserved in the fissure-filling deposits of the central carbonatic Ragusa platform. The Pleistocene mammal remains from Contrada Cimillà belong to the younger faunal association of the Hyblean Plateau. The infillings of a karstic cavity near by the Pleistocene mammal-bearing cavity at Contrada Cimillà has yielded remains of not endemic mammals (Canis sp., Erinaceus europaeus L.) as well as Neolithic artifacts.